THE RELATIONSHIP OF COGNITIVE FUNCTIONS WITH THE LEVELS OF INDEPENDENCE IN CONDUCTING ACTIVITY OF DAILY LIVING IN CANDIDATES OF ELDERLY HAJI HAJI IN KBIH KODAM I BUKIT BARISAN, MEDAN CITY - RIZKY ADITYAS WARA; ELMAN BOY S (LP2MTBM MAKARIOZ, 2021)
Decreased cognitive function in the elderly is the biggest cause of the inability to perform normal daily activities, and is alsothe most common reason that causes dependence on others to care for themselves (care dependence) in the elderly.Knowledge or cognitive is needed to meet the needs of the elderly and attitudes can also influence the behavior of theelderly in self-sufficiency in meeting the needs of daily activities. To determine the relationship of cognitive function with thelevel of independence in carrying out activity of daily living in elderly pilgrims at KBIH Kodam 1 Bukit Barisan, Medan City.The design of this study was non-experimental using a correlative analytic method with a cross sectional approach. Samplingwas done by purposive sampling. Data collection was taken through interviews using the Barthel index questionnaire andMMSE. Based on the results of the analysis test using the Chi Square test, a p value of 0.001 (p <0.05) means that there is asignificant relationship between cognitive function and the level of independence in performing ADL on the Prospective ElderPilgrims in KBIH Kodam 1 Bukit Barisan, Medan City. And based on the pearson correlation test obtained r = 0.721, whichmeans it has a strong relationship between cognitive function and the level of independence in conducting ADL on theProspective Elder Pilgrims at KBIH Kodam 1 Bukit Barisan, Medan City. There is a relationship between cognitive functionand the level of independence in carrying out activity of daily living on prospective elderly pilgrims at KBIH Kodam 1 BukitBarisan, Medan City.